MEASURING, UNDERSTANDING AND VISUALISING COAL CHARACTERISTICS-INNOVATIONS IN COAL GEOLOGY FOR THE 21ST CENTURY - Whateley M.K.G. (My University, 2002)
For the coal industry to remain competitive into the 21st century, particularly if coal prices remain low, it is incumbent upon the industry to understand their products and use this knowledge to improve the efficiency, environmental performance and safety with which their products are mined, processed and used. A full understanding of coal characterisation empowers the user to achieve these goals. Areas where coal characterisation is of crucial importance include integrated gasification and combined cycle (IGCC) combustion, metallurgical uses, gasification, extraction of coal bed methane and liquefaction. Future coal characterisation research avenues are reviewed. For this understanding to be achieved, radical new analytical methods that are cost effective, avoid subjective judgement, can provide prompt online measurements and are meaningful in terms of performance prediction will be required. Examples of emerging technologies are presented. Visualisation of coal quality data and the coal chain has always been important to the coal mining community. Methods of building and maintaining databases, and simulating such data are reviewed.
Keywords: COAL CHARACTERISATION; CONDITIONAL SIMULATION; ANALYTICAL METHODS